Recurrent Syncope Attributed to Left Main Coronary Artery Severe Stenosis - Min Li; Xinyi Zheng; Hua Liu; Yujie Liu (Case Reports in Medicine)
Patients with acute coronary syndrome (ACS) rarely manifest as recurrent syncope due to malignant ventricular arrhythmia. We report a case of a 56-year-old Chinese male with complaints of paroxysmal chest burning sensation and distress for 2 weeks as well as loss of consciousness for 3 days. The electrocardiogram (ECG) revealed paroxysmal multimorphologic ventricular tachycardia during attack and normal heart rhythm during intervals. Coronary angiograph showed 90% stenosis in left main coronary artery and 80% stenosis in anterior descending artery. Two stents sized 4.0*18 mm and 2.75*18 mm were placed at left main coronary artery and anterior descending artery, respectively, during percutaneous coronary intervention (PCI). The patient was discharged and never had ventricular arrhythmia again during a 3-month follow-up since the PCI. This indicated that ventricular tachycardia was correlated with persistent severe myocardial ischemia. Coronary vasospasm was highly suspected to be the reason of the sudden attack and acute exacerbation. PCI is recommended in patients with both severe coronary artery stenosis and ventricular arrhythmia. Removing myocardial ischemia may stop or relieve ventricular arrhythmia and prevent cardiac arrest.